2018
DOI: 10.4236/oalib.1104676
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Aspects of Malaria in Pregnant Women: Prevalence and Risk Factors in Mwene Ditu, DR Congo

Abstract: Introduction: Malaria in pregnancy induces significant risks for the mother and the foetus. The objective of this study was to determine the prevalence of malaria and the risk factors among pregnant women in the Health District of Mwene Ditu in DR Congo.Methods: A cross-sectional descriptive study based on household survey was carried out in June 2016 in the Health District of Mwene Ditu. The calculated sample size was 461 pregnant women selected through a stratified random sampling. A structured interview usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…Results from this study showed that farmers were 2.3 times at increased odds of becoming infected with malaria parasites. Similar observations were found in studies carried out in Ethiopia [ 65 ], Ghana [ 66 ], Kenya [ 67 ] and Congo [ 68 ]. This could be because these women practiced agricultural activities (a form of outdoor activity) either at dawn or dusk thus increasing the risk of them receiving infective bites from the mosquito vector [ 69 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results from this study showed that farmers were 2.3 times at increased odds of becoming infected with malaria parasites. Similar observations were found in studies carried out in Ethiopia [ 65 ], Ghana [ 66 ], Kenya [ 67 ] and Congo [ 68 ]. This could be because these women practiced agricultural activities (a form of outdoor activity) either at dawn or dusk thus increasing the risk of them receiving infective bites from the mosquito vector [ 69 ].…”
Section: Discussionsupporting
confidence: 90%
“…This could be because these women practiced agricultural activities (a form of outdoor activity) either at dawn or dusk thus increasing the risk of them receiving infective bites from the mosquito vector [ 69 ]. Moreover, reports from several studies have persistently shown an increased risk of malaria infection among individuals living in houses with many family members [ 68 , 70 , 71 ]. Study findings however demonstrated otherwise that pregnant women in households of one to three family members were 1.4 times at increased odds of being infected with malaria.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of malaria parasite among pregnant women in Zaria, Nigeria was 23.5% (Abigail, Aminu and Abdullahi, 2021) Similarly; studies from other malaria endemic parts of Africa have also reported significant variations in the prevalence of malaria parasitaemia among pregnant women. In Kenya, a prevalence of 26.1% was reported (Ter Kuile et al 2003), 12.9% in cross sectional study (Nyamu et al, 2020) in Cameroun, 82.4% (Walker et al, 2005); 25% (Asoba et al, 2009); 11.0% in Ghana in a cross sectional study (Ahad-zie et al, 2022); 10.3% in Ethopia (Gontie et al, 2020); 14.97% in DR Congo, (Jean-claude et al, 2018); 36.52% Niger Republic (Banao et al, 2010); 15.3% in Benin (Briand et al, 2020), while in Burkina Faso 21.5% (Sheick et al, 2007); 15.7% by (Yaro et al, 2021).…”
Section: Prevalence Of Malaria Among Pregnant Womenmentioning
confidence: 99%